2017
DOI: 10.1159/000455395
|View full text |Cite
|
Sign up to set email alerts
|

Personalised Medicine for Asthma and Chronic Obstructive Pulmonary Disease

Abstract: Asthma and chronic obstructive pulmonary disease (COPD) are prevalent conditions, and despite recent advances and multiple available therapies and interventions, there remains a significant unmet clinical need. In recent years, it has become clear that there is both significant heterogeneity within each of these conditions and additionally significant overlap in many of the clinical and inflammatory features. In parallel, useful clinical and immunological biomarkers which inform about prognosis and response to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 57 publications
0
15
0
1
Order By: Relevance
“…PFTs alone cannot differentiate to diagnose the right condition [5,6] . CT, however, can provide imaging-based characteristics about the lungs including measurements on lung parenchyma for detailed analyses of individual bronchi, such as small airways.…”
mentioning
confidence: 99%
“…PFTs alone cannot differentiate to diagnose the right condition [5,6] . CT, however, can provide imaging-based characteristics about the lungs including measurements on lung parenchyma for detailed analyses of individual bronchi, such as small airways.…”
mentioning
confidence: 99%
“…The role of nebulized MgSO 4 is remains to be clarified in chronic asthma [1,[24][25][26]. As a result, clinical observations suggest heterogeneity in response, most likely related to treatment intensity, the medication used, and the severity of asthma [27,28]. In one study, oral Mg 2+ was supplemented for 16 weeks, yet no differences were found in PFT, symptoms, and use of bronchodilator.…”
Section: Discussionmentioning
confidence: 99%
“…Az interjúk szerint a COPD-s betegek oktatására nagy szükség van. Érdemes ezt strukturáltan, a szakorvosok tapasztalatát felhasználva, a beteg nyelvezetének és tudásszintjének megfelelően megtenni [29]. A fentiekben bemutattuk a COPD diagnosztizáltságával, az orvos betegképével, a beteg adherenciájával és az inhalátorral kapcsolatos attitűdöket.…”
Section: Következtetésekunclassified